Step-by-step Solution

Expand the expression $\left(x+3\right)^2$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Final Answer

$x^2+6x+9$

Step-by-step explanation

Problem to solve:

$\left(x+3\right)^2$
1

A binomial squared (sum) is equal to the square of the first term, plus the double product of the first by the second, plus the square of the second term. In other words: $(a+b)^2=a^2+2ab+b^2$

  • Square of the first term: $\left(x\right)^2 = x^2$
  • Double product of the first by the second: $2\left(x\right)\left(3\right) = 2\cdot 3x$
  • Square of the second term: $\left(3\right)^2 = 3^2$

$x^2+6x+9$

Final Answer

$x^2+6x+9$

Problem Analysis

$\left(x+3\right)^2$

Main topic:

Special products

Time to solve it:

~ 0.03 seconds